2015
DOI: 10.1111/cen.12706
|View full text |Cite
|
Sign up to set email alerts
|

Molecular screening of a large cohort of Moroccan patients with congenital hypopituitarism

Abstract: This is the first molecular screening of congenital GHD in a Moroccan population and, like other studies, mutations were preferentially identified in familial cases (75%); mutations in genes such as POU1F1, HESX1, SOX3, LHX3 and LHX4 are extremely rare. The p.R73C PROP1 mutation was the most frequent mutation in CPHD; this should be the first one to screen in this population. Our results should contribute to a better diagnosis and management of this heterogeneous disease condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…However, genetic counselling remains a challenge due to variable phenotypes with incomplete penetrance and wide spectrum of anterior pituitary dysfunctions ranging from isolated deficiency to evolving panhypopituitarism. To date, several cohorts of patients with hypopituitarism have been reported from national registries 3‐5,8‐10,24 or international studies 7 . However, few provided detailed phenotypic description of CPHD patients 4,7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, genetic counselling remains a challenge due to variable phenotypes with incomplete penetrance and wide spectrum of anterior pituitary dysfunctions ranging from isolated deficiency to evolving panhypopituitarism. To date, several cohorts of patients with hypopituitarism have been reported from national registries 3‐5,8‐10,24 or international studies 7 . However, few provided detailed phenotypic description of CPHD patients 4,7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic screening of these transcription factors using a phenotype‐based strategy represents a rational way to identify aetiology of CPHD. However, defects in any of these genes have been found to date in a minority of such patients in national or international cohorts 2‐10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GH1 mutations can either lead to classical GHD (types IA, IB, and II) or bioinactive GH syndrome. While in the past the latter diagnosis was used without good experimental evidence, recent reports have shown that this is a real condition, characterized by normal or even elevated circulating GH levels, and in some cases also associated with partial GHI (28,29,30).…”
Section: Genetic Defects Of the Gh-insulin-like Growth Factor 1 Axismentioning
confidence: 99%
“…In contrast to sporadic cases, familial subjects from all countries should undergo genetic analysis if possible. In these familial cases, the likelihood of detecting a mutation within any of the transcription factor genes is much higher [ 10 16 , 19 , 20 , 33 ].…”
Section: Discussionmentioning
confidence: 99%